2007
DOI: 10.1140/epja/i2007-10498-x
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on nuclear-matter properties from QCD susceptibilities

Abstract: We establish the interrelation between the QCD scalar response of the nuclear medium and its response to a scalar probe coupled to nucleons, such as the scalar meson responsible for the nuclear binding. The relation that we derive applies at the nucleonic as well as at the nuclear levels. Non trivial consequences follow. In particular it opens the possibility of relating medium effects in the scalar meson exchange or three-body forces of nuclear physics to QCD lattice studies of the nucleon mass.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Although very attractive this picture has some problems. For instance it seems difficult to reproduce the value of the parameter κ N S characterizing the scalar response of the nucleon [5]. In such a picture the constituent quarks (or diquark) essentially move in the non perturbative vaccuum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although very attractive this picture has some problems. For instance it seems difficult to reproduce the value of the parameter κ N S characterizing the scalar response of the nucleon [5]. In such a picture the constituent quarks (or diquark) essentially move in the non perturbative vaccuum.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in ref. [5,7,8] such a significant scalar response will generate other repulsive forces which restore the saturation mechanism. At this point it is important to come again to the underlying physical picture implying that the nucleon mass originates both from the coupling to condensate and from confinement.…”
Section: B Nucleon Structure Effects and Confinement Mechanismmentioning
confidence: 99%
“…The origin of this failure can be attributed to the neglect of the effect of nucleon substructure linked to the confinement mechanism as already pointed out in some of our previous works [1,2,9]. It was demonstrated that nuclear matter stability can be restored once the scalar response of the nucleon depending on the quark confinement mechanism is properly incorporated in a way inspired from the QMC model [10].…”
Section: Introductionmentioning
confidence: 87%
“…In a previous work [22] we have introduced a model of a nucleon made of three constituent quarks bound together by a confining harmonic force. The magnitude of the scalar response which followed was too small to prevent the collapse of nuclear matter.…”
Section: Effect Of Confinement: Simple Models For the In-medium mentioning
confidence: 99%